2013
DOI: 10.1016/j.jvir.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Cartesian Acquisition with Projection-like Reconstruction Magnetic Resonance Angiography with Computed Tomography Angiography for Evaluation of below-the-Knee Runoff

Abstract: Purpose To prospectively compare the assessment of stenosis and radiologist confidence in the evaluation of below the knee lower extremity runoff vessels between computed tomographic angiography (CTA) and contrast enhanced magnetic resonance angiography (MRA) in a cohort of 19 clinical patients. Materials and Methods Our study was HIPAA compliant and IRB-approved. 19 consecutive patients with known or suspected peripheral arterial disease were imaged with both CTA and a recently developed MRA technique perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Favorable scoring seemed to follow where disease was present, with MRA typically being advantageous for more distal disease and CTA being advantageous for proximal disease and where stents were located. The first of these is consistent with previous work directly comparing CE-MRA and CTA in imaging of the calves (22). Motion and acceleration artifacts at the abdomen-pelvis station and venous contamination at the calf-foot station in cases of rapid arterial-to-venous transit are the prime issues that next need to be addressed.…”
Section: Discussionsupporting
confidence: 91%
“…Favorable scoring seemed to follow where disease was present, with MRA typically being advantageous for more distal disease and CTA being advantageous for proximal disease and where stents were located. The first of these is consistent with previous work directly comparing CE-MRA and CTA in imaging of the calves (22). Motion and acceleration artifacts at the abdomen-pelvis station and venous contamination at the calf-foot station in cases of rapid arterial-to-venous transit are the prime issues that next need to be addressed.…”
Section: Discussionsupporting
confidence: 91%
“…The image pairs were graded on a 5‐point ordinal scale from −2 to + 2, with −2 indicating a strong preference for the first image, +2 indicating a strong preference for the second image, and 0 representing no preference . The order of the rFOV and full‐FOV images in the pair was blinded to the readers.…”
Section: Methodsmentioning
confidence: 99%
“…Steady‐state MRA yields isotropic, submillimeter voxels, allowing for multiplanar reconstruction and more accurate stenosis assessment when compared with conventional first‐pass MRA techniques, thereby allowing the radiologist to differentiate luminal thrombus from calcification, which helps guide treatment options . Recent studies have also demonstrated MRA to be superior to CE‐CT angiography for the evaluation of the below‐knee runoff arteries, particularly those that are diffusely narrowed and/or diffusely calcified …”
Section: Peripheral Arterial Diseasementioning
confidence: 99%
“…24 Recent studies have also demonstrated MRA to be superior to CE-CT angiography for the evaluation of the below-knee runoff arteries, particularly those that are diffusely narrowed and/or diffusely calcified. 25 Our current protocol using a Siemens Aera 1.5T machine includes time-resolved imaging using Time resolved angiography With Stochastic Trajectories (TWIST; Siemens Healthcare, Erlangen, Germany) with a blood pool agent. Initially, 2 mL (or 20% of the contrast volume) of gadofosveset trisodium (diluted 50:50 with normal saline) is injected at 1 cc/sec with a temporal resolution of 5 seconds, imaged for 24 cycles (120 sec postinjection) to visualize the calf vessels, followed by another 8 mL (or the remainder of the contrast volume) of diluted gadofosveset trisodium and a first-pass acquisition to visualize the larger vessels with the pelvis and thigh.…”
Section: Peripheral Arterial Diseasementioning
confidence: 99%